METHODOLOGICAL APPROACHES TO TEACHING GRAMMAR (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This paper examines the methodological approaches to teaching English grammar in elementary schools, focusing on strategies that enhance both understanding and engagement among young learners. It argues for a diversified approach, integrating direct instruction, inductive learning, and contextual activities. The effectiveness of these methods in fostering grammatical competence, while maintaining student motivation and accommodating diverse learning styles, is explored through a review of current educational practices and scholarly research. One of the main aspects of the language, which was subjected to intensive discussion for many years, is the grammar of a foreign language. The attitude to grammar determined the specificty of a particular method, the principles and method of teaching, what are the main approaches in teaching English grammar, what approaches are leading in the modern conditions of teaching English and what are the main methods they are realizing.